Hydrazine Derivative-Based Carbon Dots for Potent Antibacterial Activity Against Multidrug-Resistant Bacterial - Hou-Qun Yuan; Zhu-Lin Wang; Meng-Ke Wang; Qiu-Yu Zhang; Xin-Yi Liang; Ting-Zhong Xie; Li-Ge He; Peiyao Chen; Hongda Zhu; Guang-Ming Bao (Nanomaterials)
Bacterial infections, particularly those caused by multidrug-resistant strains, remain a significant global public health challenge. The growing resistance to traditional antibiotics highlights the urgent need for novel antibacterial strategies. Herein, we successfully synthesized three types of nitrogen-doped carbon dots (tBuCz-CDs, HAH-CDs, and EC-CDs) via hydrothermal method using tert-butyl carbazate, hydroxyacetic acid hydrazide, and ethyl carbazate as precursors. tBuCz-CDs, HAH-CDs, and EC-CDs exhibited potent antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA), with minimum inhibitory concentrations (MICs) of 100, 100, and 150 µg/mL, respectively. Their antibacterial effect on MRSA was comparable to that of the widely used antibiotic vancomycin hydrochloride, as shown by the zone of inhibition assay. Furthermore, the carbon dots exhibited low cytotoxicity and hemolytic activity showing their excellent biocompatibility both in vitro and in vivo. They also significantly promoted wound healing compared to untreated controls. Notably, the serial passaging of MRSA exposed to these carbon dots did not result in the bacterial resistance. Mechanistic studies revealed that the carbon dots exerted antibacterial effects through multiple mechanisms, including the disruption of bacterial membranes, inhibition and eradication of biofilm formation, generation of reactive oxygen species, and DNA damage. This work highlights the potential of nitrogen-doped CDs as a promising material for combating drug-resistant bacterial infections and underscores their potential for further biomedical development.